The driving effect of polycentric city network on the coordinated development of regional economy in Bohai Rim region of China - Kanyong Li; Zuankuo Liu; Shuhe Shi; Kaixuan Di; Wenchao Gong; Hongkun Li (Heliyon)
Using social network analysis and spatial Dubin model, this study analyzes the data from the Bohai Rim Economic Zone between 2003 and 2019 and examines the driving effect and mechanism of polycentric urban networks on the regional economic coordination of the Bohai Rim Economic Zone of China from the perspective of combining agglomeration externality and network externality. The results show that: There is a positive correlation between the polycentric degree of the city network in the Bohai Rim Region and its coordinated economic development level; After controlling the classical production factors such as physical capital, non-central cities narrow the gap between their per capital income level and the central cities, and produce positive spatial spillover effects by increasing the relative node centrality in the process of embedding in the polycentric urban network; On the whole, small and medium-sized cities gain node agglomeration growth effect, medium-sized cities play a positive spillover effect, and large cities with node centers play a long wave radiation effect, breaking through geographical proximity—these three factors are interlocked. This research offers pivotal insights for refining the spatial configuration of the Bohai Economic Rim. Moreover, the findings provide policy recommendations to enhance China's regional spatial structure, facilitating the progression of regional economies on a broader scale and to loftier standards.